ZmNAC074, a maize stress-responsive NAC transcription factor, confers heat stress tolerance in transgenic Arabidopsis - Xi, Yan; Ling, Qiqi; Zhou, Yue; Liu, Xiang; Qian, Yexiong (Frontiers in Plant Science, 2022)
The harsh environment such as high temperature greatly limits the growth, development and production of crops worldwide. NAC (NAM, ATAF1/2, and CUC2) transcription factors (TFs) play key regulatory roles in abiotic stress responses of plants. However, the functional roles of NAC TFs in heat stress response of maize remain elusive. In our present study, we identified and isolated a stress-responsive NAC transcription factor gene in maize, designated as ZmNAC074 and orthologous with rice OsNTL3. Further studies revealed that ZmNAC074 may encode a membrane-bound transcription factor (MTF) of NAC family in maize, which is comprised of 517 amino acid residues with a transmembrane domain at the C-terminus. Moreover, ZmNAC074 was highly expressed and induced by various abiotic stresses in maize seedlings, especially in leaf tissues under heat stress. Through generating ZmNAC074 transgenic plants, phenotypic and physiological analyses further displayed that overexpression of ZmNAC074 in transgenic Arabidopsis confers enhanced heat stress tolerance significantly through modulating the accumulation of a variety of stress metabolites, including reactive oxygen species (ROS), antioxidants, malondialdehyde (MDA), proline, soluble protein, chlorophyll and carotenoid. Further, quantitative real-time PCR analysis showed that the expression levels of most ROS scavenging and HSR- and UPR-associated genes in transgenic Arabidopsis were significantly up-regulated under heat stress treatments, suggesting that ZmNAC074 may encode a positive regulator that activates the expression of ROS-scavenging genes and HSR- and UPR-associated genes to enhance plant thermotolerance under heat stress conditions. Overall, our present study suggests that ZmNAC074 may play a crucial role in conferring heat stress tolerance in plants, providing a key candidate regulatory gene for heat stress tolerance regulation and genetic improvement in maize as well as in other crops.